SINERGI BAITUL MAAL DAN BMT DALAM MENDORONG PENGEMBANGAN EKONOMI DESA SUMURGEDE - Zaini Syahrurromdhoni; Darmawan (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2024)
Sumurgede Village, despite being categorized as a developing village, still faces significant challenges related to poverty. The majority of its residents rely on an under- optimized agricultural sector. Underdeveloped infrastructure and limited market access also hinder economic development. In this context, Baitul Maal and BMT play strategic roles. BMT provides Sharia-based financing for MSMEs, while Baitul Maal distributes zakat funds for business capital. These institutions not only provide access to capital but also business mentoring, which is crucial in reducing poverty and improving community welfare. The synergy between Baitul Maal and BMT has proven effective in supporting local economic development through a sustainable approach in accordance with Sharia principles.